Assessment of systemic and pulmonary arterial remodelling in women with systemic sclerosis. (3rd September 2015) - Irzyk, K; Bienias, P; Rymarczyk, Z; Bartoszewicz, Z; Siwicka, M; Bielecki, M; Karpińska, A; Dudzik-Niewiadomska, I; Pruszczyk, P; Ciurzyński, M
Abstract : Objectives: Systemic sclerosis (SSc) leads to pulmonary circulation dysfunctionand there are some indications of systemic circulation impairment. We evaluated the influence of SSc on the elastic properties of large systemic arterial walls and potential correlations between systemic and pulmonary circulation involvement. Method: We examined 75 consecutive women (mean age 53.13 ± 10.1 years) with confirmed SSc [mean disease duration (DD) 7.1 ± 9.1 years] and 21 age-matched female volunteers (mean age 52.6 ± 8.3 years, ns). Pulse wave velocity (PWV) and transthoracic echocardiography were performed. SSc patients were divided into two groups according to the median of DD: ≤ 3 years (39 patients) and > 3 years (36 patients). Results: Patients with DD > 3 years had higher PWV than those with DD ≤ 3 years and controls (log PWV: 2.23 ± 0.23 vs. 2.13 ± 0.16 and vs. 2.11 ± 0.16 m/s; p = 0.028 and 0.029, respectively). In addition, echocardiographic indices showed impaired right ventricular (RV) function in the patients with DD > 3 years. Also in these SSc patients, PWV correlated with clinical and echocardiographic parameters of pulmonary circulation: age (r = 0.64, p < 0.0001), acceleration time of pulmonary ejection (AcT; r = −0.38, p = 0.021), and tricuspid regurgitation peak gradient (TRPG; r = 0.34, p = 0.04). Multiple linear regression analysis showed that PWV was independently associated with DD (β = 0.22, p = = 0.02), AcT (β = −0.215, p = 0.03), and age (β = 0.44, p < 0.001). Conclusions: In patients with SSc lasting more than 3 years, the disease is characterized by increased stiffness of the large systemic arteries. Longer duration of SSc leads simultaneously to the increased stiffness of the large systemic arteries and to the progressive impairment of RV function and its coupling to the pulmonary arterial bed.